Estudo de tempos e métodos em uma empresa de alimentos embutidos localizada no interior do Rio Grande do Norte - Araújo, Matheus Fábio do Nascimento (Universidade Federal Rural do Semi-Árido, 2019)
In an environment of recurring change, companies must be prepared to continually innovate and thereby improve their management system. This article has as main objective the application of a study of times and methods in a company of embedded foods located in the city of Timbaúba dos Batistas-RN. Initially, a broad literature review was performed and the study application site was chosen. The research was conducted between April and July 2019, in which technical visits were made for data collection. It is characterized as a descriptive and exploratory case study of a quantitative and qualitative nature.For data collection and processing, we used MS Excel software, version 2016, Bizagi Modeler, version 3.4.1.068, as well as cronoanalysis instruments. As a result, it was possible to make the flowchart of the main production process of the company, which contains 31 operations, the determination of the standard times of each activity, where it was noticed that the boning operation is the one that consumes the most time (TP = 165.45 seconds). Finally, POPs were built to standardize the activities performed by each employee, as well as suggestions for enlargements for future work, such as man-machine graphics.
Artigo
Keywords: Mapeamento; Estudo de tempos; Cronoanálise; Procedimento operacional; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA